La motricidad fina en el proceso de la escritura los niños y niñas de 6 y 7 años de edad en la educación general básica de la escuela Vicente León del cantón Quero, provincia de Tunguragua el año lectivo 2014- 2015 - Ritta Jeannette, Estupiñán Villafuerte (2015)
In the “Vicente Leon high school the teachers have studied the importance of this theme, they in a correct way consider that the fine motor is really important because of it is very important in the global develop of the child, therefore the motor is like a science, technique and it is an environment of differences in the childhood develop and as in social effective as in the driving way (physics, biological and functional). Thus, we will develop the perspective and driving interference, like a helping process that will attach to the boy or girl in their schedule process of growing, and it will notice their expressions since their driving demonstrations till to get the higher process as a language or a thought, we mean, everything we know about the set of their psychomotor expression. This set is recognize principal aspects, that they are part of the globally; the social-affectivity, the motor; the cognition and their communicative expression. In the group of boys and girls that are 6 and 7 years old in the General Basic School we have noticed some difficulties in the fine motor in the moment of write, draw and paint on other due that we know the motor develop however it is not accomplish in a good way in the correct age of children that must done. It is a worried situation in the teachers especially in the higher levels because the writing way it is not so good, generating some smooth in the process learning – teaching, that is the reason why we must create new processes that will help children where boys and girls can develop a real good fine motor and improve their way of writing and achieve their proposed objectives, so parents, teacher can interfere on time in their motor develop in their children allowing positive showing in the process of writing. My theme “ The motor fine in the process of writing in the children between 6 and 7 years old in the General basic education” Quero in the Province of Tungurahua during 2014-2015 school year. It is drifted from the set problem, and this problem has basing researches by different authors that they are right to get a method like experiment with the learning, in this school, the “Vicente Leon School” the children have no idea what motor fine can contribute in their own develop of learning. As a general objective we have determined to value the motor fine as an important factor, so to develop the skills of the writing learning with boys and girls which is released from the specific objectives. We proposed an hypothesis so we identified the independent and depending variables, to operationalize in a demonstrative table, this allowed us to design the questions to create the interview. In the chapter related to the Theorist setting, we registered some topics and subtopics the biggest importance that our research is scientifically base with the support of some researchers and pedagogues we have structured the basis of our concept in the field of the real process of learning. In the same chapter, we presented the legal Mark, with some establish disposals that mean the obligation to educate our children, their rights, their shelters, etc. we also present the Conceptual Theory, the terms, and the most important phrases that were used in the scientific theory that illustrate the purpose of our research. And finally we wrote the Referential Theory, where w present how to stimulate the real learning develop and also the history of the school that they have allowed advance this research. This is the resume of our theory that support our investigation and also to the research institution in the social context, educative politic. In the chapter three where it is developed the analysis and the interpretation of results, with the correct tables, graphics, and analysis, that they allowed state then the conclusions, recommendations and check our hypothesis. Finally, in the chapter four we will propose an alternative to solve urgent problem, through a guide of didactic activities that must be put on with the teacher in the boys and girls the psychomotor social, affective aspects, until achieve their fullness in love, dynamism, liking and functional in their study and application in a new substantial learning.